PENGARUH PEMBERIAN KONSENTRASI GULA TERHADAP DAYA TAHAN SIMPAN SIRUP MANGGA ARUMANIS - Mawar Simahate; Rahmadina Rahmadina (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2020)
Arumanis mango syrup is a thick juice produced from the flesh of the mango fruit arummanis with the addition of liquid sugar as a natural preservative to maintain durability save syrup. This research aims to know the concentration of sugar with a variation of different sugars can provide durability syrup mango fruit is longer. This type of research is research using the method of experimentation with proven influence durability save syrup fruit mango arummanis with 40% sugar, sugar 50%, 60%, 70%. The result showed that the concentration of sugar in the variation of 40% have staying power save syrup fruit mango fruit mango is low, i.e., on the 7th day already moldy syrup, sugar concentration at 50% also already moldy on day 8. Note that the concentration of sugar in the variation of 40% and 50% have a staying power save syrup mango fruit is lower, at 60% and sugar concentration of 70% have good conditions until the day to 27. This suggests that the higher the concentration of sugar then endurance save syrup mangoes will be increasingly long.